Answer:3/
Step-by-step explanation:
<u>Answer:</u>
<u>Solution:</u>
-x - 6y = -23
<u>Now, let's substitute the value of y into the first equation.</u>
- x + 4y = 17
- => x + 4(3) = 17
- => x + 12 = 17
- => x = 5
<u>Let's check our answer to make sure it is correct.</u>
<u>Check:</u>
- -x - 6y = -23
- => -(5) - 6(3) = -23
- => -5 - 18 = -23
- => -23 = -23
Hence, this is proven correct.
Hoped this helped.
All I could think is subtract and divide
Answer:
wheres the picture
Step-by-step explanation:
Answer:
2p+2q
Step-by-step explanation: